Livestock Products Food Expenditure Pattern in Indonesia: Estimation Analysis From Repeated Cross-Section Data - Muzayyanah, Mujtahidah Anggriani Ummul (2017)
The aim of this study is to analyze the livestock products consumption patterns based on a household data and explore thr dynamic effects as well as al the impact of demographic variables on the demand model specification .This paper used a dynamic LA/AIDS demand model to estimate varios food demand parameters for household using household expenditure survey data (SUSENAS)2012 and 2013. The results show that all important livestock products food has positive expenditure elasticities . Meat,egg and milk are necessities.The estimated point elasticities are consistent with previous studies and a priori expectations.Egg is found to be price inelastic in the long run. While meat and milk are price elastic in the long run. The expenditure elasticities for meat and milk are declining ,but these for egg is increasing.As per capita income rises and population increase, the demand fot these items will continue to increase. Habit effects imply consumption of livesoctk products having an income effect on current consumption decision Therefore, Indonesia must continue to increase its food production by a greater rate in the future in order to avoid food shortages